A review of phase change heat transfer in shape-stabilized phase change materials (ss-PCMs) based on porous supports for thermal energy storage - Zhang, Shuai; Feng, Daili; Shi, Lei; Wang, Li; Jin, Yingai; Tian, Limei; Li, Ziyuan; Wang, Guoyong; Zhao, Lei; Yan, Yuying (Elsevier, 2020)
Latent heat thermal energy storage (LHTES) uses phase change materials (PCMs) to store and release heat, and can effectively address the mismatch between energy supply and demand. However, it suffers from low thermal conductivity and the leakage problem. One of the solutions is integrating porous supports and PCMs to fabricate shape-stabilized phase change materials (ss-PCMs). The phase change heat transfer in porous ss-PCMs is of fundamental importance for determining thermal-fluidic behaviours and evaluating LHTES system performance. This paper reviews the recent experimental and numerical investigations on phase change heat transfer in porous ss-PCMs. Materials, methods, apparatuses and significant outcomes are included in the section of experimental studies and it is found that paraffin and metal foam are the most used PCM and porous support respectively in the current researches. Numerical advances are reviewed from the aspect of different simulation methods. Compared to representative elementary volume (REV)-scale simulation, the pore-scale simulation can provide extra flow and heat transfer characteristics in pores, exhibiting great potential for the simulation of mesoporous, microporous and hierarchical porous materials. Moreover, there exists a research gap between phase change heat transfer and material preparation. Finally, this review outlooks the future research topics of phase change heat transfer in porous ss-PCMs.